ANALISIS KINERJA KEUANGAN KSP ARTHA AGUNG ABADI KELURAHAN TLUMPU KECAMATAN SUKOREJO BLITAR - Maylla Mazayu; Tri Kurniastuti; Luhur Aditya Prayudi; Yuhanin Zamrodah (grafting, 2022)
The study aims to determine or measure the results of financial performance in savings and loans cooperatives in 2019-2021 based on the analysis of liquidity ratios, solvency, rentability, activity. The method used during the study is to use quantitative descriptive. Data analysis techniques use healthy or unhealthy ratios. The results of the calculation of the Current Ratio for 2019-2021 of 190.12%, 198.13%, 207.20% are said to be unhealthy. The Dept to Asset Ratio for 2019-2021 of 53.50%, 50.47% 42% is said to be quite healthy. The Debt to Equity Ratio for 2019-2021 11.06%, 101.90%, 82.45% is said to be a fairly healthy category. Return On Asset in 2019-2021 of 3.50%, 2.86%, 3.10% is said to be unhealthy. Return on Equity in 2019-2021 of 7.52%, 5.78%, 6.01% is said to be unhealthy. Receivables turnover in 2019-2021 of 105.56%, 104.30%, 104.14% is said to be healthy. Asset turn Over 0.33, 0.34, 0.38 is said to be healthy.